Megaloblastic Anemia + E. Coli-Induced Diarrhea = Trouble - Engelbert Buxbaum; Thomas Butler; Rajdeo Kalliecharan; Bruce Wright; Aidi Yin (Association of American Medical Colleges, 2013)
Abstract Introduction Physicians experience consistent environmental pressures while doing thier work. To give students practice making clinical decisions in a time- and cost-limited scenario, we created this group learning, case-based activity for first-year medical students during their second semester. During this activity students are tasked with diagnosing a pediatric patient who presents with traveler's diarrhea, but also signs of an underlying chronic anemia. Methods This 2-hour session began with students reviewing the case in groups of 8 for 15 minutes after which time they were allowed to purchase physical exam results, and later test results from a simulated lab. However, all student groups had a limited number of tokens which restricts what information they could buy. After a set time, students presented their diagnosis and there was a facilitated discussion. The exercise was followed by 5-6 NBME-style multiple choice questions on the basic science related to this case. Each question was presented and student groups had 60-90 seconds to respond via an electronic audience response system. To evaluate the session, students were given an IRB-approved, Likert scale questionnaire via Survey Monkey. Results This type of exercise was originally developed for our scholars, which includes 150 students. However, we have run such cases also with the entire class of 500 students. Even though the preparation is more laborious than a typical group learning exercise, faculty find this fun to do. Students, too, like this format; the majority think the additional simulated pressure is more helpful than normal clinical cases. Discussion This type of exercise has also been used for remedial work with students. Lab-token exercises may also be appropriate in the training of other health care workers (e.g., nurse practitioners).